2015
DOI: 10.1111/his.12853
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph nodes for breast carcinoma: an update on current practice

Abstract: Sentinel lymph node (SLN) biopsy has been established as the standard of care for axillary staging in patients with invasive breast carcinoma and clinically negative lymph nodes (cN0). Historically, all patients with a positive SLN underwent axillary lymph node dissection (ALND). The ACOSOG Z0011 trial showed that women with T1-T2 disease and cN0 who undergo breast conserving surgery and whole-breast radiotherapy can safely avoid ALND. The main goal of SLN examination should be to detect all macrometastases (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 147 publications
(167 reference statements)
0
35
0
Order By: Relevance
“…For BC, the SLN is usually located in the ipsilateral axilla, which makes the axillary lymph node (ALN) status an important prognostic factor and determinant for the treatment of patients with mammary adenocarcinomas, who constitute the vast majority of the BC cases. 3,4 The procedure is that BC patients who initially show no sign of metastatic axillary disease on ultrasonography (US) analysis or needle biopsy will have an SLN biopsy (SLNB) performed during the surgical procedure in which the primary tumour is removed. This procedure has been internationally established as the standard of care for axillary staging in BC patients with invasive BC without initial US signs of lymph node metastasis (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For BC, the SLN is usually located in the ipsilateral axilla, which makes the axillary lymph node (ALN) status an important prognostic factor and determinant for the treatment of patients with mammary adenocarcinomas, who constitute the vast majority of the BC cases. 3,4 The procedure is that BC patients who initially show no sign of metastatic axillary disease on ultrasonography (US) analysis or needle biopsy will have an SLN biopsy (SLNB) performed during the surgical procedure in which the primary tumour is removed. This procedure has been internationally established as the standard of care for axillary staging in BC patients with invasive BC without initial US signs of lymph node metastasis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7][8] This has led to dramatic changes in the clinical management of the axilla. 3 Local and systemic therapies have progressed from initially assessing ALN status only, to integrating all involved nodes, and to investigating the tumour burden of individual nodes. 2 The introduction of SLNB and assessment of individual nodes in the axillary staging of BC has led to the application of more extensive time-consuming and costly pathological examination techniques, such as serial sectioning and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel lymph node biopsy (SLNB) is the current standard of care for determining axillary lymph node involvement in patients with clinically node‐negative breast cancer, having an accuracy between 93.5% and 97.5% . However, the complications of SLNB, while typically less than those associated with axillary lymph node dissection, include increased operation time, additional surgical scars, painful preoperative injections, and possible false‐positive results . To reduce the number of patients having unnecessary surgical SLNB, previous studies have suggested methods for identifying patients with metastatic lymph nodes preoperatively .…”
mentioning
confidence: 99%
“…[ 17 , 18 ] Though the novel methods of lymphoscintigraphy confer their own unique advantages in reducing the FNR of SLNB in preclinical studies, their application in practice depends upon further prospective clinical studies to identify suitable protocols, and the uptake of such advanced methods might require some time. [ 19 21 ]…”
Section: Discussionmentioning
confidence: 99%